2009
DOI: 10.1371/journal.pone.0008283
|View full text |Cite
|
Sign up to set email alerts
|

Erk1 and Erk2 Regulate Endothelial Cell Proliferation and Migration during Mouse Embryonic Angiogenesis

Abstract: Angiogenesis is a complex process orchestrated by both growth factors and cell adhesion and is initiated by focal degradation of the vascular basement membrane with subsequent migration and proliferation of endothelial cells. The Ras/Raf/MEK/ERK pathway is required for EC function during angiogenesis. Although in vitro studies implicate ERK1 and ERK2 in endothelial cell survival, their precise role in angiogenesis in vivo remains poorly defined. Cre/loxP technology was used to inactivate Erk1 and Erk2 in endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 53 publications
10
117
0
3
Order By: Relevance
“…However, the blockade of γ-secretase activity did not affect FGF-2-induced cell migration. The importance of MAPK and PI3K signaling pathways in FGF-2-induced endothelial cell migration was also confirmed by previous studies [55,56]. Here, PI3K blockade results in a full inhibition of BAEC migration induced by mCRP, while mCRPinduced distance of cell migration was remained unaffected after either MAPK or γ-secretase blockade.…”
Section: Discussionsupporting
confidence: 87%
“…However, the blockade of γ-secretase activity did not affect FGF-2-induced cell migration. The importance of MAPK and PI3K signaling pathways in FGF-2-induced endothelial cell migration was also confirmed by previous studies [55,56]. Here, PI3K blockade results in a full inhibition of BAEC migration induced by mCRP, while mCRPinduced distance of cell migration was remained unaffected after either MAPK or γ-secretase blockade.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have demonstrated that integrin signaling through FAK plays an important role in the regulation of cell cycle progression correlating with changes in the expression of cyclin D1 [16]. In another study, ERK acts downstream of Src-FAK signaling [17,18] and upstream to regulate FAK and Paxillin expression [19]. In the present study we found that c-Myc associates and interacts with FAK.…”
Section: Fig 3 Effect Of Hucbsc Treatment and Sherk Transfections Osupporting
confidence: 69%
“…9). Although it has been reported that Arf6 is required for activation of MAPK ERK1/2 and the small G protein Rac1 in HGFstimulated epithelial cells 20 , which are implicated in endothelial cell migration 31,32 , no difference in activation of MAPKs, such as ERK1/2, p38 and JNK, Akt and Rac1 was observed for Arf6 À / À iECs in comparison with control iECs (Supplementary Fig. 10), eliminating these signalling pathways and outputs from further consideration.…”
Section: Endothelial Arf6 Regulates Tumour Angiogenesis and Growthmentioning
confidence: 89%